The effect of changes in oil price and monetary stance on stock market performance – Evidence from Bursa Malaysia - Abdul Razak, Abdul Hadi (Universiti Malaysia Perlis (UniMAP), 2011)
The 2nd International Conference on the Roles of Humanities and Social Science in Engineering (ICoHSE 2010) organized by Universiti Malaysia Perlis (UniMAP), 12th - 14th November 2010 at Bayview Beach Resort, Penang, Malaysia.